EFFECTS OF OUTPATIENT PULMONARY REHABILITATION ON LUNG FUNCTION IN PATIENTS WITH CHRONIC OBSTRUCTIVE PULMONARY DISEASE: AN INTEGRATIVE REVIEW (CIPEEX, 2025)
INTRODUCTION: Chronic obstructive pulmonary disease (COPD) is a condition characterized by persistent airflow limitation accompanied by progressive airway obstruction. COPD is a significant cause of death globally, associated with reduced quality of life and hospitalization. Pulmonary rehabilitation (PR) is based on specific therapies to improve the patient's condition. It is an important factor in COPD cases as it relates to lung function, which assesses forced expiratory volume in the first second (FEV1) and forced vital capacity (FVC) using a spirometer. OBJECTIVE: To demonstrate the effects of outpatient pulmonary rehabilitation on lung function in patients with COPD. METHODOLOGY: Based on the objective, 7 original articles were chosen, selected through a search in the PubMed (Public Medline), VHL (Virtual Health Library), and SciELO (Scientific Electronic Library Online) databases, found using the Boolean operator "and", utilizing the Health Science Descriptors (DeCS) "Chronic obstructive pulmonary disease", "Rehabilitation" and "Quality of Life". RESULTS: The lung function of the sample was an important indicator to measure the effectiveness of outpatient PR, consisting of physical exercises, guidance, and lifestyle changes; however, there were discrepancies between studies. CONCLUSION: It is evident that outpatient PR is an important tool in the treatment of COPD, as observed through spirometry measures, where the sample that underwent PR showed improvement or maintenance mainly in FEV1; however, this cannot be taken as an established fact.
Keywords: Chronic Obstructive Pulmonary Disease; Pulmonary rehabilitation; Lung function